Ultra-small MOSFETs: The Importance of the Full Coulomb Interaction on Device Characteristics. Issue 1 (2001) - Gross, W. J.; Vasileska, D.; Ferry, D. K.
Abstract : We discuss a full three-dimensional model of an ultra-small MOSFET, in which the transport is treated by a coupled EMC and molecular dynamics (MD) procedure to treat the Coulomb interaction in real space. The inclusion of the proper Coulomb interaction affects both the energy and momentum relaxation processes, but also has a dramatic effect on the characteristic curves of the device. We find that the short-range e – e and e –i terms, combined with discrete impurity effects, is also needed for accurate measurement of the device threshold voltage.